CORRELATIONAL STUDY STUDENTS’ MOTIVATION AND ENGLISH LEARNING ACHIEVEMENT - Suyanto, Suyanto; Supardi, Iwan; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractMotivation plays an important role to the success of the students’ learning. Each individual who has motivation will drive directly to achieve his goal to facilitate himself. Motivation needed to reach a successful of English learning achievement. This research has porposes to find out how high the students’ motivation and students’ English learning achievement, how strong the correlation between students’ motivation and English learning achievement and investigate the most dominant factor influencing students’ low English learning achievement. The population of this research was the eleventh grade students of MAS Hidayatul Muslimin 2 Sungai Raya. They were 20 students as the samples from 34 were students. The method of this research was conducted correlational study. The data collected from the questionnaire and documentary. From the reserach finding, the data analysis showed that the students’ motivation was clarified moderate qualification with mean score 50.2% and the students’ English achievement was categorized poor with mean score 38.6. The correlation between students’ motivation and English learning achievement is categorized low with r = 0.34 and the contribution of motivation on English learning achievement was 34%. It was low impact to contribute the students’ English learning achievement, it might be caused by other factor. Last, the most dominant factor influencing students’ low English learning achievement was clarified students’ attitude. Students have negative attitude toward English subject. Most of them did not pay good attention while the learning teaching process in the classroom and the school also was lack of media and facilities to support them in learning English. Keyword: Correlational Study, Students’ Motivation, English Learning Achievement